Hubungan Promosikesehatan Dan Keselamatan Kerja, Pelatihan Tenaga Kerja Dengan Penerapan Penggunaan Pestisida Terhadap Cholinestrase Darah Pada Gapoktan Tanjung Sehati Yang Bersertifikat Roundtable On Sustainable Palm Oil (Rspo)Di Kabupaten Merangin - Rosyani; Ermanto; Sukmal Fahri (Universitas Jambi, 2019)
Oil palm farmers effort is still low to use safe pesticides, occupational safety and health promotion is rarely carried out for workers and unfulfilled for increasing of workers’ knowledge with training. Occupational exposure to pesticides as a possible high risk factors for workers. The purpose of research is to know relationship occupational safety and health promotion, training of workers and application of pesticide use to blood cholinesterase at Tanjung Sehati Farmer Institution is certified by roundtable on sustainable palm oil in Merangin. Research method was observational analytic study by using cross sectional. This research was conducted in June to October 2018. The Samples were 66 farmer institutions by using proportional random sampling. Data analysis was conducted by descriptive and analytical by Chi Square teston the alpa: 5%.The results of the research were obtained by blood cholinesterase of farmer institution as result of mold poisoning as 50 (75,8%), occupational safety and health promotion to farmer institution who didn’t get promotion as 55 (83,3%),workers training to farmer institution who didn’t get training as 54 (84,%), using pesticide to farmer institution who didn’t environment-friendly as 52 (78.8%). The results of the analysis is showed that there was a association between occupational safety and health promotion (p-value = 0.008 OR 7,05), There was a relationship between workers training (p-value = 0.014 OR 5,75); and the application of pesticide use to farmer members;There was a relationship between the application of pesticides with blood cholinesterase in farmer members (p-value = 0.030 OR 4,78).The conclusion was the association between occupational safety and health promotion, training of workers and the application of pesticide use to farmer members; There was a relationship between the application of pesticides with blood cholinesterase to Tanjung Sehati farmer members who have been already certified by roundtable on sustainable palm oil in Merangin.